Haematological parameters and coagulation in umbilical cord blood following COVID-19 infection in pregnancy. (November 2021) - Murphy, Claire A.; O'Reilly, Daniel P.; Edebiri, Osasere; Weiss, Luisa; Cullivan, Sarah; EL-Khuffash, Afif; Doyle, Emma; Donnelly, Jennifer C.; Malone, Fergal D.; Ferguson, Wendy; Drew, Richard J.; O'Loughlin, John; et al.
Highlights: COVID-19 infections can cause hypercoagulability and hematological derangements. Adverse perinatal outcomes and placental abnormalities are described in pregnancy. The clinical outcomes were similar in the COVID group compared to healthy controls. No evidence of haematological abnormalities or hypercoagulability in cord blood. Some reassurance about neonatal haematological outcomes of COVID in pregnancy. Abstract: Objective: The aim of this study was to evaluate infants, born to women with SARS-CoV-2 detected during pregnancy, for evidence of haematological abnormalities or hypercoagulability in umbilical cord blood. Study design: This was a prospective observational case-control study of infants born to women who had SARS-CoV-2 RNA detected by PCR at any time during their pregnancy (n = 15). The study was carried out in a Tertiary University Maternity Hospital (8, 500 deliveries/year) in Ireland. This study was approved by the Hospital Research Ethics Committee and written consent was obtained. Umbilical cord blood samples were collected at delivery, full blood count and Calibrated Automated Thrombography were performed. Demographics and clinical outcomes were recorded. Healthy term infants, previously recruited as controls to a larger study prior to the outbreak of COVID-19, were the historical control population (n = 10). Results: Infants born to women with SARS-CoV-2 had similar growth parameters (birth weight 3600 g v 3680 g, p = 0.83) and clinical outcomes to healthy controls, such as need for resuscitation at birth (2 (13.3%) v 1 (10%), p = 1.0) and NICU admission (1 (6.7%) v 2 (20%), p = 0.54). Haematological parameters (Haemoglobin, platelet, white cell and lymphocyte counts) in the COVID-19 group were all within normal neonatal reference ranges. Calibrated Automated Thrombography revealed no differences in any thrombin generation parameters (lag time (p = 0.92), endogenous thrombin potential (p = 0.24), peak thrombin (p = 0.44), time to peak thrombin (p = 0.94)) between the two groups. Conclusion: In this prospective study including eligible cases in a very large population of approximately 1500 women, there was no evidence of derangement of the haematological parameters or hypercoagulability in umbilical cord blood due to COVID-19. Further research is required to investigate the pathological placental changes, particularly COVID-19 placentitis and the impact of different strains of SARS-CoV-2 (particularly the B.1.1.7 and the emerging Delta variant) and the severity and timing of infection on the developing fetus.